Behavioral psychology of men and women in Islam - Abdillah, Aufa (Faculty of Dakwah and Communication, Walisongo State Islamic University, 2024)
Purpose - This research aims to explore gender roles in the context of behavioral psychology from an Islamic perspective, focusing on the neuropsychological differences between men and women. Method - The methodology employed is a qualitative library-based approach, involving the analysis of relevant literature sources, including journals, books, and Islamic texts. This study collects data from reputable academic sources and Islamic texts to build a comprehensive understanding of gender roles and the associated neuropsychological aspects. Result - The findings indicate that the gender roles described in Islam may reflect certain neuropsychological function differences, which can influence the quality of life and dynamics of social interactions. It is important to note that while biological and psychological differences between men and women exist, both are often viewed as having equal social responsibilities within religious and moral contexts. Implication - This study implies that there is a need for Muslim men and women to be aware of their obligations according to sharia and nature . Originality/Value - The specialty of this study is that it explains neuropsychological concepts to understand the psychological behavior of women and men. *** Tujuan - Penelitian ini bertujuan untuk mengeksplorasi peran gender dalam konteks psikologi perilaku dari perspektif Islam, dengan fokus pada perbedaan neuropsikologis antara pria dan wanita. Metode - Metodologi yang digunakan adalah pendekatan kualitatif berbasis kepustakaan, yang melibatkan analisis sumber-sumber literatur yang relevan, termasuk jurnal, buku, dan teks-teks Islam. Penelitian ini mengumpulkan data dari sumber-sumber akademis terkemuka dan teks-teks Islam untuk membangun pemahaman yang komprehensif tentang peran gender dan aspek-aspek neuropsikologis yang terkait. Hasil - Temuan menunjukkan bahwa peran gender yang dijelaskan dalam Islam dapat mencerminkan perbedaan fungsi neuropsikologis tertentu, yang dapat memengaruhi kualitas hidup dan dinamika interaksi sosial. Penting untuk dicatat bahwa meskipun terdapat perbedaan biologis dan psikologis antara laki-laki dan perempuan, keduanya sering dipandang memiliki tanggung jawab sosial yang sama dalam konteks agama dan moral. Implikasi - Penelitian ini menyiratkan bahwa ada kebutuhan bagi pria dan wanita Muslim untuk menyadari kewajiban mereka sesuai dengan syariah dan kodrat. Orisinalitas/Nilai - Nilai dari penelitian ini adalah mampu menjelaskan konsep neuropsikologi untuk memahami perilaku psikologis perempuan dan laki-laki.